Canning of Smoked Dhoma (Sciaenid sp.) - GIRIJA VARMA, P R; VENKATARAMAN, R (Fishery Technology, 2017)
A process for the preparation of a wholesome smoked and canned product from dhoma (Sciaenid sp.) is discussed. The dressed dhoma is cold blanched in 15% brinecontaining 0.5% potash alum and 0.2% citric acid and smoked for 120 minutes at45 Â± 5Â°C. The smoked fish after filling in cans is precooked at 0.35 kg/sq.cm steampressure for 50 minutes in inverted position, filled with hot refined groundnut oil,sealed and processed for 60 minutes at 0.7 kg/sq. cm steam pressure